Corporate Governance (Board of Directors and Audit Committee Characteristics) and Firm Performance. (Global Business Management Review (GBMR), 2022)
The study aims to empirically investigate the relationship between corporate governance (Board and Audit Committee characteristics) and firm performance of firms listed on the Saudi Stock Exchange. The study will be based on the premise (agency theory) that corporate governance (board and audit committee characteristics) is associated with the firm performance. Data will be gathered from all companies during the year 2009. The board characteristics variables are independence, activities, size, stock ownership (at the level of the board) and board chairman stock ownership. The audit Committee characteristics are independence, activities, size, stock ownership (at the level of the audit committee), audit committee chair stock ownership, interactions with internal auditors and interactions with external auditors. Two measures of firm performance that are return on assets (ROA) and operating cash flow (OCF) will be considered.